Doclea, Montenegro. Eine römische Stadt in Illyrien. Die Begehung des Jahres 2019 - Oettel, Andreas; Živanović, Miloš (e-Forschungsberichte des DAI, 2020)
The Roman city of Doclea in Montenegro was excavated between 1890 and 1892 and published by Piero Sticotti in 1913. The city has a forum and several temples, but it seems to lack residential quarters. Inscriptions point to the city’s founding in the Flavian period, but it may also be possible that it was founded in the Augustean period. A planned German-Montenegrin project aims to carry out new excavations as well as to reexamine the areas already excavated. The potential of such investigations already became evident during a first visit. A newly found relief fragment and a well-known gable relief can be assigned to a temple, which so far has hardly been noticed.